Spatial Variability of Urban Quality of Life in Kirkos Sub-City (Addis Ababa) - Tesfazghi, E. S. (CRC Press, 2020)
This chapter is structured as follows. After this introduction (Section 8.1), Section 8.2 discusses relevant literature on QoL domains and attributes, as well as providing our justification for the domains of life identified in this study. Section 8.3 considers methodological aspects, in particular the methods of data collection and analysis. The results of the study, such as descriptive statistics on domain satisfaction, spatial variability of satisfaction levels for different domains and a multiple regression analysis of the relation between QoL and domains, are presented in Section 8.4. Context and policy implications are also presented in Section 8.4. Finally, conclusions are presented in Section 8.5.